A 16S rRNA Gene-Based Metabarcoding of Phosphate-Rich Deposits in Muierilor Cave, South-Western Carpathians - Haidău, Catalina; Năstase-Bucur, Ruxandra; Bulzu, Paul; Levei, Erika; Cadar, Oana; Mirea, Ionuţ Cornel; Faur, Luchiana; Fruth, Victor; Atkinson, Irina; Constantin, Silviu; Moldovan, Oana Teodora (Frontiers in Microbiology, 2022)
Muierilor Cave is one of Romania's most important show caves, with paleontological and archaeological deposits. Recently, a new chamber was discovered in the cave, with unique yellow calcite crystals, fine-grained crusts, and black sediments. The deposits in this chamber were related to a leaking process from the upper level that contains fossil bones and a large pile of guano. Samples were taken from the new chamber and another passage to investigate the substrate and microbial community relationship. Chemical, mineralogical, and whole community 16S rRNA gene-based metabarcoding analyses were undertaken, and the base of the guano deposit was radiocarbon dated. Our study indicated bacteria linked to the presence of high phosphate concentration, most likely due to the nature of the substrate (hydroxyapatite). Bacteria involved in Fe-, Mn-, or N- cycles were also found, these elements being commonly identified in high concentrations in guano. Since no bat colonies or fossil bones are present in the new chamber, a high concentration of these elements could be sourced by organic deposits inside the cave (guano and fossil bones) even after hundreds of years of their deposition and in areas far from both deposits. Metabarcoding of the analyzed samples found that 0.7% of the identified bacteria are unknown to science, and 47% were not previously reported in caves or guano. Moreover, most of the identified human-related bacteria were not reported in caves or guano before, and some are known for their pathogenic potential. Therefore, continuous air and floor microbiology monitoring should be considered in show caves with organic deposits with bacteria that can threaten human health. The high number of unidentified taxa in a small sector of Muierilor Cave indicates the limited knowledge of the bacteria diversity in caves that can have potential applications in human health and biotechnology.